KEMATIAN DAN MASA ANTARA - Bungalan, Jhon Efrendi; Salurante, Tony (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2024)
The research problem focuses on the differing perspectives between Christianity and the beliefs of the Saluan community regarding the concept of death and the existence of the soul after death. In Christianity, death is viewed as the final separation of the body and soul. In contrast, in the beliefs of the Saluan community, the soul undergoes a transitional phase known as the Periode Ton. This study aims to analyze the similarities and differences in the concepts of death and the existence of the soul after death in both belief systems. The research employs a qualitative method with a literature review approach. Data were collected from various sources, including books, scholarly journal articles, and previous research findings. The data were analyzed using the Miles and Huberman model, including data reduction, presentation, and conclusion drawing. The findings indicate that while there are similarities in understanding death as the separation of body and soul, significant differences exist in the existence and influence of the soul after death. In the beliefs of the Saluan community, the soul remains in the physical world until the Mohatu ritual is performed. In contrast, Christianity asserts that the soul immediately enters the presence of God or is separated from Him. In conclusion, this study contributes to contextual theology by integrating cross-cultural understanding.